Monoclonal antibodies binding to different epitopes of CD20 differentially sensitize DLBCL to different classes of chemotherapy - Lee, Brian; Pierpont, Tim; August, Avery; Richards, Kristy (Frontiers in Oncology, 2023)
Rituximab, an anti-CD20 monoclonal antibody and the world's first approved antibody for oncology patients, was combined with the CHOP chemotherapy regimen and markedly improved the prognosis of all B-cell derived lymphomas. However, there is a 35% disease recurrence with no advancement in first-line treatment since rituximab was combined with the archetypal CHOP chemotherapy regimen nearly 30 years ago. There is evidence that rituximab synergizes with chemotherapy, but pharmacological interactions between rituximab and CHOP, or between newer anti-CD20 mAbs and CHOP, remain largely unexplored. Using in vitro models, we discovered vast heterogeneity in pharmacological interactions between rituximab and CHOP in a way not predicted by the current clinical classification. We then unexpectedly discovered that rituximab and ofatumumab differentially synergize with the cytotoxic and cytostatic capabilities of CHOP in separate distinct subsets of DLBCL cell lines, thereby expanding favorable immunochemotherapy interactions across a greater range of cell lines beyond those induced by R-CHOP. This finding was completely unexpected because these monoclonal antibodies were long considered to be biological and clinical equivalents, but in practice, may perform better than the other in a patient-specific manner. This finding may have immediate clinical significance because both immunochemotherapy combinations are already FDA-approved with no difference in toxicity across phase I, II, and III clinical trials. Therefore, this finding could inform a new precision medicine strategy to provide additional therapeutic benefit to B-cell lymphoma patients using immunochemotherapy combinations that already meet the clinical standard of care.